Behavioral, Thermal and Neurochemical Effects Of Acute And Chronic 3,4-Methylenedioxymethamphetamine (“Ecstasy”) Self-Administration - Reveron, Maria Elena (2009)
3,4-methylenedioxymethamphetamine (MDMA) is a popular methamphetamine derivative associated with young adults and all-night dance parties. However, the enduring effects of MDMA at voluntary intake levels have not been extensively investigated. In this study, MDMA-influenced behaviors and core temperatures were assessed over the course of 20 daily MDMA self-administration sessions in rats. In vivo microdialysis techniques were used in a subsequent MDMA challenge test session to determine extracellular nucleus accumbens dopamine (NAcc DA) and serotonin (5-HT) levels in MDMA-experienced and naïve animals before and after a self-administered MDMA injection (3.0 mg/kg, i.v.). During self-administration sessions, gradual and significant increases in MDMA intake and MDMA-stimulated locomotor activity were observed across sessions. Core temperature significantly decreased during initial MDMA sessions, but was unaltered by the last 10 sessions. In the MDMA challenge test, MDMA-naïve rats showed significantly higher NAcc 5-HT responses compared to MDMA-experienced rats, though MDMA experience did not affect the magnitude of NAcc DA response. The overall findings suggest that changes in MDMA-induced responses over the course of increasing levels of drug exposure may reflect the development of tolerance to a number of MDMA effects.